IMPACT OF INSTRUCTIONAL MATERIALS ON ACADEMIC PERFORMANCE ADULT LEARNERS IN MASALLACI NATIONAL MODEL ADULT EDUCATION CENTER, SHAHUCI, KANO STATE - HALILU, AUWALU; TUKUR, ABBA MUHAMMAD (Sokoto Educational Review, 2023)
The study examined the impact of instructional materials on academic achievement of adult learners in Masallaci National Model Adult Education Center, Shahuci, Kano State. The objectives of the study are to identify the available instructional materials, determine the impact of instructional materials on academic performance of adult learners, and to examine the factors promoting the use of Instructional Materials in Masallaci National Model Adult Education Center, Shahuci, Kano State. Mixed design. Pre-test and post-test research design was adopted for the study. The population of the study is 2,600 adult learners. Simple random samplings technique was used for the selection of the sample of 335 adult learners in line with Krejcie and Morgan. The instruments for data collection were questionnaire and achievement test. Instrument was taken to the supervisor and experts in adult education, education and special education, the instrument there after was corrected and validated and the researcher used test-re-test methods the scores obtained from the two different administration process were entered into SPSS and correlated to obtained reliability coefficients of 0.69 and 0.70 respectively for the two instruments. Data collected were analyzed using simple percentage, frequency counts, mean and standard deviation. The findings were that the instructional materials available in the center include pictures, models. Instructional materials are very effective on the academic achievement of adult learners in Masallaci National Model Adult Education Center, Shahuci, Kano State. That the nature of the subject matter during lesson, nature of the objectives to be attained and high number of learners involved during lesson are the factors promoting the use of instructional materials in the center. The study recommend that instructional materials should be provided in adult education centers especially videos, audios and audio-visuals. The subject matter and the lesson objectives should always be written in a clearer way to enhance the effective selection of appropriate instructional materials. The number of learners in each class should be regulated to a controllable size so as to enhance the effectiveness in the utilization of the instructional materials in the center.